DEVELOPMENT OF INDONESIAN-BASED TEACHING MATERIALS INTERACTIVE EDUCATIONAL GAME "PEBI "TO IMPROVE READING SKILLS IN THE BEGINNING OF GRADE II ELEMENTARY SCHOOL STUDENTS - Imas Mastoah; Zulela MS; Mohamad Syarif Sumantri; Wawan Gunawan (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Interactive Educational Game is a game that aims to provoke children's interest in learning the subject matter while playing, so that with a happy feeling it is hoped that children can more easily understand the subject matter presented. This study aims to develop Indonesian language teaching materials based on interactive educational games to improve the early reading skills of second grade elementary school (SD) students. This study uses the Research and Development Research method using the Dick and Carey Model. The Dick and Carey model is one of the learning design models with a systems approach. Based on the results of the research on the Development of Indonesian Language Teaching Materials Based on Interactive Educational Games "PEBI" Class II SDN Mekar Jaya Serang Regency, it can be concluded several things as follows: (1) Development of Indonesian Language Teaching Materials Based on Interactive Educational Games "PEBI" was developed based on an analysis of teacher needs and students through a needs questionnaire provided by the developer, (2) The results of the validation of material experts, media experts, and design experts on the development product of Indonesian Language Teaching Materials Based on the "PEBI" Interactive Educational Game with very feasible criteria to be developed, and (3) Based on the results Research on the development of Indonesian Language Teaching Materials Based on Interactive Educational Games "PEBI" can be concluded that the Digital Book learning media is used in developing abilities in designing creative, innovative and interesting learning.